Thermal history and basin evolution of the Moatize - Minjova Coal Basin (N'Condedzi sub-basin, Mozambique) constrained by organic maturation levels - Galasso, Francesca (2021)
Kerogen concentrates obtained from Lopingian (Late Permian) to Upper Triassic mudrock lithologies of seven coal exploration boreholes, drilled in the Moatize - Minjova Coal Basin (N'Condedzi sub-basin, Mozambique), were studied by means of vitrinite reflectance (VR), spore fluorescence and spore colour, in order to constrain the thermal history and basin evolution by organic maturation levels. VR increases with depth, indicating organic maturation related to sediment burial for most of the boreholes. Modelled VR data indicate a regional palaeogeothermal gradient between 35 and 40 degrees C/km. Lower Jurassic doleritic intrusions observed in three boreholes had only local thermal effects without affecting the regional palaeogeothermal gradient. Two boreholes located near the basin margin show high palaeogeothermal gradients suggesting thermal processes other than heating due to burial were involved. These processes may have involved hot diagenetic fluids circulating through fault zones and/or permeable lithologies, locally elevating geothermal gradients. Circulation of these fluids was induced by lithostatic pressure due to rapid rates of sedimentation. These high sedimentation rates lead to the accumulation of a thick succession (over 2000 m) of Lopingian (Late Permian) to Upper Triassic siliciclastic sediments. All the organic maturation indices measured and the age of the successions indicate that organic maturation occurred during or after Late Triassic times. However, the presence of reworked Permian palynomorphs into Upper Triassic sediments and the absence of Middle Triassic sediments indicate an exhumation and erosion of Permian strata in Middle Triassic times. The organic maturation levels of the reworked palynomorph population are considerably higher than the indigenous Upper Triassic population, indicating that they attained higher burial temperatures prior to being reworked.